Trends in Acute Lymphoblastic Leukemia Incidence in the United States by Race/Ethnicity From 2000 to 2016 - Feng, Qianxi; de Smith, Adam J; Vergara-Lluri, Maria; Muskens, Ivo S; McKean-Cowdin, Roberta; Kogan, Scott; Brynes, Russell; Wiemels, Joseph L (American journal of epidemiology, 2021)
Abstract Incidence trends in acute lymphoblastic leukemia (ALL) demonstrate disparities by race and ethnicity. We used data from the Surveillance, Epidemiology, and End Results Registry to evaluate patterns in ALL incidence from 2000 to 2016, including the association between percentage of people born in a foreign country at the county level and ALL incidence. Among 23,829 persons of all ages diagnosed with ALL, 8,297 (34.8%) were Latinos, 11,714 (49.2%) were non-Latino (NL) Whites, and 1,639 (6.9%) were NL Blacks. Latinos had the largest increase in the age-adjusted incidence rate (AAIR) of ALL during this period compared with other races/ethnicities for both children and adults: The AAIR was 1.6 times higher for Latinos (AAIR = 2.43, 95% confidence interval (CI): 2.37, 2.49) than for NL Whites (AAIR = 1.56, 95% CI: 1.53, 1.59) (P < 0.01). The AAIR for all subjects increased approximately 1% per year from 2000 to 2016 (annual percent change = 0.97, 95% CI: 0.67, 1.27), with the highest increase being observed in Latinos (annual percent change = 1.18, 95% CI: 0.76, 1.60). In multivariable models evaluating the contribution of percentage of county residents who were foreign-born to ALL risk, a positive association was found for percentage foreign-born for NL Whites (P for trend < 0.01) and NL Blacks (P for trend < 0.01), but the reverse was found for Latinos (P for trend < 0.01); this is consistent with tenets of the “Hispanic paradox,” in which better health outcomes exist for foreign-born Latinos.